THE REPRESENTATION OF FILIATION AND AFFILIATION TOWARDS HISPANIC-AMERICAN COMMUNITY ON NETFLIX SERIES “ON MY BLOCK’ BY LAUREN IUNGERICH - Widodo, Jordy Satria; Suendarti, Mamik; Syamsudin, Oom Rohmah (Universitas Pakuan, 2023)
On My Block (2018) series, directed by Lauren Iungerich and aired on Netflix in 2018, tells the story of four friends who live in a block in the city of Los Angeles, United States. Chaos often occurs due to the presence of many Hispanic gangsters. Cesar, one of four friends, faces a dilemma between following his family's wishes to become the successor to a gangster named Santos in his area or going to school for a better future with his friends. The dilemma faced by Cesar can be described as a negotiation between filiative and affiliative relations as elaborated by Edward Said (1978). Affiliation is a gift and cannot be changed which is passed down from generation to generation in the family, whereas affiliation is obtained through social interaction with other people. Cesar himself negotiated between filiates and affiliates which in the end, he preferred the filiate to become the head of the Santos gangsters in the block. This film shows a different story plot from other youth films set in slum areas in America which emphasize that success is only shown through education at school. This series instead presents the success achieved by Cesar through his choice as head of the Santos gangsters. However, another character, Monse, who is an African Hispanic woman, decides to go to higher education which is different from Cesar's choice. So, this series shows the construction of the Hispanic-American version of the American Dream which is shown through strong filial ties.